The role of humoral autoimmunity in gastrointestinal neuromuscular diseases. - Hubball, A; Martin, J; Lang, B; De Giorgio, R; Knowles, C (2009)
Dysfunction of the gastrointestinal neuromuscular apparatus (including interstitial cells of Cajal) is presumed to underlie a heterogeneous group of disorders collectively termed gastrointestinal neuromuscular diseases (GINMDs). There is increasing experimental and clinical evidence that some GINMDs are immune-mediated, with cell-mediated dysfunction relatively well studied. Humoral (antibody)-mediated autoimmunity is associated with several well-established acquired neuromuscular diseases and is now implicated in an increasing number of less well-characterised disorders, particularly of the central nervous system. The role of autoimmunity in GINMDs has been less studied. Whilst most work has focused on the presence of antibodies directed to nuclear antigens, particularly in the context of secondary disorders such as paraneoplastic intestinal pseudo-obstruction, the possibility that 'functional' anti-neuronal antibodies directed to membrane-bound ion channels may cause disease (channelopathy) is now also being realised. The evidence for humoral autoimmunity as an etiologic factor in primary (idiopathic) and secondary GINMDs is systematically presented using the original paradigms previously applied to established autoimmune neuromuscular disorders. The presence of anti-enteric neuronal antibodies, although repeatedly demonstrated, still requires the identification of specific neuronal autoantigens and validated evidence of pathogenicity.